Prehospital airway management by health workers in Riyadh City: A local survey - Hatun Fahad Al-Rajeh; Faisal F. Alshehri; Rayyan M. Alhaqbani; Alwaleed S. Almalki; Nora B. Barakah; Nuha M. Albaqami; Saud A. Alhasoun; Fawaz Alafandi; Azzam Nawab (Saudi Journal of Emergency Medicine)
This study sought to determine the perception of healthcare workers (HCWs) about pre-hospital airway management and their experiences. Methods: This cross-sectional study was conducted among health workers at the emergency department of King Fahad Medical City in the capital of Saudi Arabia, Riyadh City. This study targeted physicians, nurses, paramedics, and respiratory therapists. Data were collected using an online questionnaire. The questionnaire included demographic characteristics, training, and experiences in airway management and a 5-item questionnaire to measure the perception of HCWs about airway management. Results: Of the 100 HCWs, 39% were doctors, and 37% were nurses. Approximately 23% had a poor experience with intubation. Traumatic injuries were the major difficulties involving airway management (44%). The overall perception of HCWs about prehospital airway management was good (68%), 31% were moderate, and only 1% were considered poor perception levels. No significant differences were observed between perception scores in relation to the demographic characteristics and experiences of HCWs in airway management (all p>0.05). Conclusion: Despite HCWs' good perception of prehospital airway management, some gaps have been identified mainly through intubation skills and experiences. This study provided evidence that perception towards prehospital airway management was not affected by profession, years of experience, regular practice of intubation, and airway management. Regular training should be implemented, with equipment and resources should be available to improve airway management and patient quality of care. [SJEMed 2024; 5(2.000): 128-133]